73.5k views
9 votes
X (27-x) = 182
Please help me by solving this!​

1 Answer

3 votes

We are provided with a expression as follows ;


  • {\sf x(27-x)=182}

Can be further written as ;


{: \implies \quad \sf 27x-{x^(2)}=182}


{: \implies \quad \sf {x^2} -27x + 182=0}

Using splitting the middle term we have ;


{: \implies \quad \sf {x^2} - 13x-14x+182=0}


{: \implies \quad \sf x(x-13)-14(x-13)=0}


{: \implies \quad \sf (x-13)(x-14)=0}

Case I :-

When , (x-13)=0 , then clearly x = 13

Case II :-

When , (x-14)=0 , then clearly x = 14

Hence , The required values of x are 13 and 14 respectively

User Snowbound
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.